Alih Kode dan Campur Kode Pada Keluarga Bapak Wahyudi Di Kampung Cibitung - Alinda Dita Putri Wahyu Sagita; Sinta Rosalina (Peneliti.net, 2023)
Research objectives describethe phenomenon of code switching and code mixing occurred in Mr. Wahyudi's family environment in Cibitung village. As well asdescribefactors affecting code switching and code mixingfamily Mr. Wahyudi in the village of Cibitung. This study uses a qualitative approach and analytic descriptive method. Data collection techniques using in-depth interview techniques and participant observation. Data analysis collection techniques include data reduction, data presentation, and drawing conclusions or verification. The results of the analysis show that there is code switching and code mixing in the speeches of Wahyudi's family in Cibitung village. Factors affecting code switching and code mixingfamily Mr. Wahyudi in Cibitung village, namely the speaker presents the third person, the speaker's habits, and the insertion of words.